A Gold‐Nanoparticle‐Based SERS Reporter that Rolls on DNA Origami Templates. Issue 10 (14th September 2017) - Liu, Bing; Ren, Shaokang; Xing, Yikang; Teng, Nan; Wang, Jun; Zhu, Dan; Su, Shao; Peng, Hongzhen; Wang, Lihua; Wang, Lianhui; Chao, Jie
Abstract: Plasmonic nanostructures with distinct spatial configuration and geometry are of considerable significance because of their desired optical response. These optical responses have close relationship with the inter‐particle parameters in plasmonic nanostructures. However, the precise control of the consecutive variation of these parameters remains a formidable challenge. Here, we demonstrate a gold nanoparticle (AuNP) ‐based plasmonic nano‐reporter, in which a AuNP performs as a walker to stepwise roll directionally and progressively on DNA origami. Using another AuNP as a stator, the rolling of the AuNP reporter could generate the inter‐particle distance variation, which would be monitored by surface‐enhanced Raman scattering (SERS). Our method opens up a door to develop an optical reporter that monitors inter‐particle variations in plasmonic nanostructures. Abstract : A gold nanoparticle (AuNP)‐based plasmonic nano‐reporter is demonstrated, in which a AuNP performs as a walker to stepwise roll directionally and progressively on DNA origami. Using another AuNP as a stator, the rolling of the AuNP reporter could generate the inter‐particle distance variation, which would be monitored by surface‐enhanced Raman scattering (SERS).